THE USE OF ANIMATED VIDEO IN IMPROVING STUDENTS' READING SKILL (A Quasi-Experimental Study of Seventh Grade Student at A Junior High School in Jalancagak, Subang) - Hanifah Khalidiyah (Journal of English and Education, 2015)
The study entitled “The Use of Animated Video in Improving Students' Reading Skill” was aimed to investigate the effectiveness of the use of animated video in improving students’ reading skill, and to examine students’ perception toward animated video technique. The research used quasi-experimental design with pre-test and post-test. The sample consists of 30 of 9th grade junior high school students in Jalancagak. The findings of the research indicated that the animated video was significantly effective in improving students’ reading comprehension. It can be seen from the results that were analyzed statistically using SPSS v20. The calculation showed that there are differences of students’ learning outcomes before and after the treatment. Moreover, it is emphasized by the questionnaire results that showed most of the students gave positive responses toward the use of animated video, which are the animated video improving their reading comprehension, motivating them, stimulating their interest and increasing their curiosity. From this research, the teachers are recommended to have better competencies in selecting and presenting animated video in teaching reading.